Identification of PEG 6000 concentrations for assessing drought resistance in millet genotypes during the seed germination phase - O. V. Gorlachova; S. N. Gorbachova; V. S. Lutenko; O. V. Anceferova (Труды по прикладной ботанике, генетике и селекции)
Background. Using LD50 concentrations of the osmotic PEG 6000 to select millet genotypes during seed germination for drought resistance breeding is the best way of millet genotype differentiation according to the studied trait.Materials and methods. The millet cultivars ‘Omriyane’, ‘Kharkovskoe 57’, ‘Konstantinovskoe’, ‘Slobozhanskoe’, and the accession IR 5 were selected as the test material. Water stress was applied through five concentrations of PEG (6000 MW): 11.5%, 15.3%, 19.6%, 23.5%, 28.9%, and 0.0% (control). On the sixth day of incubation, millet seed germination was measured. The regression method for assessing LD50 (half-lethal dose) by V. B. Prozorovskii was used to theoretically substantiate the selection of an optimal osmotic concentration, which would be most accurate in identifying the level of drought tolerance in millet genotypes during seed germination.Results and conclusions: The 15.3% to 28.9% concentrations of PEG 6000 solutions had a negative effect on seed germination of millet genotypes. A strongly suppressed seed germination rate was observed at the PEG concentration of 23.5%: germination percentage in all cultivars (except for IR 5, with 56.0%) fell below 50%. Calculations according to the Verhulst logistic curve and the probit analysis by V. B. Prozorovskii’s technique showed that the mean LD50 concentration of PEG 6000 solutions for all studied genotypes was 23.03%. Thus, as a result of the analysis of our experimental data and their statistical processing, we recommended the 23.0% concentration of PEG 6000 solution as the most differentiating in terms of drought resistance in the millet seed germination phase.